2016
DOI: 10.1186/s12872-016-0192-8
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3A attenuates cardiac autonomic disorders and reduces inducible ventricular arrhythmias in rats with experimental myocardial infarction

Abstract: BackgroundTo investigate the effects of semaphorin 3A (sema 3A) on cardiac autonomic regulation and subsequent ventricular arrhythmias (VAs) in post-infarcted hearts.Method and resultsIn order to explore the functions of sema 3A in post-infarcted hearts, lentivirus-Sema 3A-shRNA and negative control vectors were delivered to the peri-infarcted myocardium rats respectively. Meanwhile, recombinant sema 3A and control (0.9 % NaCl solution) were injected intravenously into infarcted rats to test the therapeutic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…In the present study, we implanted bilateral stainless steel guide cannulas into the PVN to microinject LY294002. The NE concentration [21] and RNSA [2] were higher in the MI groups than in the control groups, which was consistent with previous studies and suggested enhancement of sympathetic excitability in rats post-MI. Targeted regulation of sympathetic activity by microinjection of LY294002 into the PVN in MI rats ameliorated the peripheral sympathetic excitability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we implanted bilateral stainless steel guide cannulas into the PVN to microinject LY294002. The NE concentration [21] and RNSA [2] were higher in the MI groups than in the control groups, which was consistent with previous studies and suggested enhancement of sympathetic excitability in rats post-MI. Targeted regulation of sympathetic activity by microinjection of LY294002 into the PVN in MI rats ameliorated the peripheral sympathetic excitability.…”
Section: Discussionsupporting
confidence: 92%
“…The electrophysiological study was performed as reported previously [14,21]. Electrodes and the epicardial surface of the LV meshed together tightly.…”
Section: Electrophysiological Studymentioning
confidence: 99%
“…Cardiac-specific overexpression of Sema3a induces a reduction of sympathetic innervation and transgenic animals display susceptibility to ventricular tachycardia 44 . Accordingly, it has been reported that myocardial overexpression of Sema3a 45 or intravenous administration of recombinant Sema3A protein 46 after infarction in rats can reduce the probability of ventricular tachycardia that frequently is an associated response to injury, as a result of attenuated sympathetic reinnervation. Moreover, a nonsynonymous polymorphism (I334V, rs138694505A>G) in exon 10 of the human SEMA3A gene was associated with unexplained cardiac arrest and ventricular fibrillation; the axon repelling activity SEMA3A I334V appears significantly weaker of that of its wild type counterpart and in the hearts of patients sympathetic nerves invade the subendocardial layer 47 …”
Section: Sema3amentioning
confidence: 99%
“…The inhibition effect of the high glucose environment on osteoblast differentiation may be a consequence of multiple mechanisms, including activating pyroptosis pathway, increasing ROS production ( Rezaeepoor et al, 2018 ), and activating GSK3β ( Hu et al, 2016a ). However, there are several limitations that need to be addressed in future study.…”
Section: Discussionmentioning
confidence: 99%